Ciudad montaje: hyper-clusters (2020)
The project explores architecture through utopic and dystopic imaginaries which primly shaped the main idea of the investigation. It evolves by considering the positive and negative space within a city, the full and the vacant. The project analyses vague spaces and therefore creates a new surface that both plays and contains the emptiness, transforming the uncertain space into a livable one. The modular system as public infrastructure pretends to create a bridge between what's already there and its new surface, it also explores the possibilities of urban sprawl considering the human scale its main design source.